The Relationship Between Serum Endocan Level and Aortic Elastic Properties in Patients With Newly Diagnosed Essential Hypertension. (August 2019) - Çelik, Mustafa; Sökmen, Erdoğan; Sivri, Serkan; Uçar, Cahit; Nar, Rukiye; Erer, Murat
Endothelial dysfunction plays role in the generation of both essential hypertension (EH) and aortic stiffness. We evaluated the relationship between serum endocan level and aortic elastic properties (AEPs) assessed with the aortic strain, aortic distensibility, and aortic stiffness index by echocardiography. Newly diagnosed EH patients (n = 67) and controls (n = 70) were included in the study. The EH group was subdivided into stage 1 and 2 EH groups. A higher endocan level was found in the EH group, compared to the controls (34.2 ± 13.0 vs 24.1 ± 7.3 ng/mL, respectively, P < .001). All the AEP parameters were worse in the EH group, compared to the controls. Further, endocan levels correlated with aortic distensibility ( r = −0.305, P < .001) and aortic strain ( r = −0.181, P = .038), but not with aortic stiffness index ( r = 0.162, P = .064) in the whole study population. Aortic elastic properties deteriorate and serum endocan level increases in patients with EH. Moreover, serum endocan level shows a correlation with deteriorated AEPs, and hence may a surrogate marker of escalating aortic stiffness in patients with newly diagnosed EH.